Effects of exercise and dietary polyunsaturated fatty acid on blood lipid profiles of streptozotocin-induced diabetes in rats - Abu Hassim, Hasliza; Mohamed Mustapha, Noordin; Goh, Yong Meng (Universiti Putra Malaysia Press, 2011)
The efficacy of exercise and dietary polyunsaturated fatty acid (PUFA) on streptozotocin-induced diabetes in rats was investigated based on blood lipid profiles, with respect to triglycerides, total cholesterol, high-density lipoprotein (HDL)-cholesterol, and low-density lipoprotein (LDL)-cholesterol. A total of 32 Sprague-Dawley male rats were used and divided into eight groups. Four groups were exercised daily for 8 weeks, while the other four were sedentary. Treatment diets were defined as follows: rat chow diet only (Control diet), rat chow added with 2:1, menhaden oil:soybean oil (Diet 1), rat chow added with 1:2, menhaden oil:soybean oil (Diet 2), and rat chow added with 10% (w/w) butter (Diet 3). Blood plasma was collected at the end of 8 weeks for blood lipid profiles determination. The results showed that a combination of exercise and dietary PUFA significantly improved lipid abnormalities by lowering the triglycerides, total cholesterol, and LDL-cholesterol levels.